2007
DOI: 10.1002/pi.2146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organo‐montmorillonite on the mechanical and morphological properties of epoxy/glass fiber composites

Abstract: Epoxy composites filled with glass fiber and organo-montmorillonite (OMMT) were prepared by the hand lay-up method. The flexural properties of the epoxy/glass fiber/OMMT composites were characterized by a three-point bending test. The flexural modulus and strength of epoxy/glass fiber were increased significantly in the presence of OMMT. The optimum loading of OMMT in the epoxy/glass fiber composites was attained at 3 wt%, where the improvement in flexural modulus and strength was approximately 66 and 95%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…However, the epoxy resin absorbs high degree of moisture which in turn degrades the functional, structural and mechanical properties of the composites [11]. In our previous studies, it was found that the optimum loading of OMMT in epoxy/glass fiber nanocomposites is attained at 3 wt% [12]. The combination of glass fiber and organo-montmorillonite could give a synergistic effect on the improvement of mechanical properties for epoxy through hand-lay up technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, the epoxy resin absorbs high degree of moisture which in turn degrades the functional, structural and mechanical properties of the composites [11]. In our previous studies, it was found that the optimum loading of OMMT in epoxy/glass fiber nanocomposites is attained at 3 wt% [12]. The combination of glass fiber and organo-montmorillonite could give a synergistic effect on the improvement of mechanical properties for epoxy through hand-lay up technique.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that not only modifying the fibre surface but also adding various fillers into the matrix can dramatically enhance the interfacial properties of fibre reinforced composites, in particular the addition of inorganic nanoparticles . For example, since polarity and structure are similar between phyllosilicate sheet and the surface of glass fibre, the interfacial bonding between glass fibre and resin was greatly improved by the addition of phyllosilicate sheet …”
Section: Introductionmentioning
confidence: 99%
“…5,6 For example, since polarity and structure are similar between phyllosilicate sheet and the surface of glass fibre, the interfacial bonding between glass fibre and resin was greatly improved by the addition of phyllosilicate sheet. 7,8 Graphene is a two-dimensional material consisting of sp 2 -hybridized carbon atoms arranged in a honeycomb structure and possesses high specific surface area, excellent mechanical properties and high electrical and thermal conductivity. 9 All these remarkable properties make graphene an ideal filler for modifying fibre reinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have described GFRPs with different matrices, for instance, epoxy [1], PA [2,3], PBT [4], etc. The amount of GFs is a crucial factor in GFRPs.…”
Section: Introductionmentioning
confidence: 99%